Rapid membrane effect of estrogens on stimulation of corticotropin-releasing hormone. (July 2020) - Qi, Yang-Jian; Fang, Zheng; Ren, Zhong; Wu, Juan-Li; Guo, Lei; Tan, Hong; Huang, Man-Li; Shen, Yi; Bao, Ai-Min
Highlights: Membrane-initiated estrogen signaling (MIES) stimulates corticotropin releasing hormone (CRH). MIES stimulate CRH by increasing nitric oxide (NO) synthesis. PI3K plays a major role in MIES -mediated CRH stimulation via increased NO synthesis. MIES upregulates CRH also via PKC, independent of NO synthesis. MIES is a key target in the rapid stress responses. Abstract: Background: Classic nuclear-initiated estrogen signaling stimulates corticotropin-releasing hormone (CRH) gene expression as a transcription factor. However, the possible mechanism by which membrane-initiated estrogen signaling (MIES) influences CRH expression remains unclear. There are indications that MIES may upregulate nitric oxide (NO) production through the phosphatidylinositol 3-hydroxy kinase (PI3K) and potentially through the mitogen-activated protein kinase (MAPK) pathway. Objectives: We investigated the effect of MIES-mediated kinase pathways on CRH expression with or without NO synthesis. Method: In SK-N-SH cell culture, estradiol-bovine serum albumin (E2-BSA) was used as the specific membrane estrogen receptor activator, with a specific NO donor, and/or inhibitors for NO synthase (NOS), PI3K, MAPK, protein kinase A (PKA), and protein kinase C (PKC). Results: E2-BSA significantly increased NO and CRH levels in the medium and NOS1-mRNA levels in the cells. In addition, NO donor up-regulated CRH expression, while NOS-inhibitor down-regulated it. When the inhibitor of MAPK and/or the inhibitor of PI3K was added to the medium, only the latter appeared to significantly block the stimulating effect of E2-BSA on NO synthesis, and this was accompanied by an increased CRH expression in the medium. We further studied the effect of the MIES-PKC-mediated pathway on CRH expression, with or without NOS-inhibitor, while the MIES-PKA(-PI3K) pathway served as a control. We found that MIES-PKC upregulated CRH expression independent of NO synthesis. Conclusion: MIES can efficiently upregulate CRH expression via various intracellular kinase pathways and may thus be a crucial component in the stress response.